In vitro bulblet regeneration from Pancratium maritimum twin scale explants - Gür, Nazmi; Kadıköylü, Gülce; Özdemir, Fethi Ahmet; Topdemir, Aykut; Düzel, Ahmet (My University, 2015)
The sea daffodil (Pancratium maritimum) is a perennial Mediterranean dune plant belonging to the Amaryllidaceae family. Because of steadily increasing urban expansion and other human activities, the species intensively lost their natural habitats and was characterized as endangered and protected in Bulgaria, Greece and recently, it was classified as threatened in France, Spain, Italy and Turkey. Therefore, it is necessary to develop protocols for the propagation of this plant in large number including biotechnological approaches. The study reports multiplication of plants by using 1 cm length bulb twin scale explants. Twin scale explants were cultured on MS medium containing 0.5, 1, 2 mg/L BAP and 1, 2 mg/L NAA (6 combinations). Variable regeneration was observed this explants. Maximum number of bulblets was observed on MS medium containing 0.5 mg/L BAP and 1 mg/L NAA. The rooting was achieved on MS medium containing 1 mg/L IBA. The highest rooting was recorded on 0.26 cm diameter bulblets and maximum long roots was recorded 4.8±0.3 cm. The rooted bulblets were easily hardened in the growth chamber and aclimatised in greenhouse.
Bildiri - Yayımlanmamış
Keywords: Pancratium maritimum; Bulblet; Regeneration; Twin scale